g+11=9

Simple and best practice solution for g+11=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g+11=9 equation:


Simplifying
g + 11 = 9

Reorder the terms:
11 + g = 9

Solving
11 + g = 9

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + g = 9 + -11

Combine like terms: 11 + -11 = 0
0 + g = 9 + -11
g = 9 + -11

Combine like terms: 9 + -11 = -2
g = -2

Simplifying
g = -2

See similar equations:

| 20-3x-2x= | | 8y+x=13x+20 | | 2(x-y)+3(x-y)= | | 9x+8.32=7x+11 | | 6x-2+4=-20 | | 19/5=5k/5 | | -5.8+1.1x=4.5 | | 123=3x-3 | | 3x+2=2[2x+1] | | 12.85=x-4.34 | | 2-3/8=13 | | 5+.25m=50 | | -6=10p/7 | | 6-3p=-0 | | 4x-5=2x+4 | | 12z^2-7z+6=0 | | 60x^3-390x=0 | | 5u=45 | | y=9lnx^3 | | 5[x+1]=20 | | 3z+2z=5z | | 30=a | | 5x-10t=3 | | 8x^2+5=517 | | 3(x+4)+2(x+2)=41 | | 6b+18=7b+-21 | | 3b-24b= | | 5(5m-4)+11=66 | | (2w+2)(4w-1)=4w+1 | | 13=20+X | | x-3/8=15/8 | | 3x+20=9x-4 |

Equations solver categories